Regenerative Endodontic Procedure in an Immature Permanent Incisor with Internal Root Resorption: a Case Report - Gaizka Loroño; Antonio Jesús Conde; Roberto Estévez; Claudia Brizuela; Ruth Pérez Alfayate (Shiraz University of Medical Sciences, 2022)
This report describes a regenerative endodontic procedure of an immature permanent incisor with internal root resorption (IRR) and 4-years follow-up. A healthy 8-year-old man was referred for treatment of tooth #9 after a traumatic intrusion. The periapical radiograph showed an IRR and an open apex with periradicular lesion. A diagnosis of pulp necrosis and chronic apical abscess was achieved. In the first appointment, under local anesthesia and rubber dam isolation, an access cavity was designed and the root canal was chemically cleaned under irrigation with 10 mL 1.5% sodium hypochlorite (NaOCl). The root canal was then dried and calcium hydroxide paste was placed. During the second appointment, the root canal was irrigated with 5 mL of 17% ethylenediaminetetraacetic acid (EDTA) for 5 minutes and dried. The blood clot was established in a time of 3 minutes after the bleeding from the periapical tissue was trigged. White mineral trioxide aggregate (MTA) was placed up to the amelocemental junction and the final restoration of the access cavity was carried out. During periodic clinical and radiographic follow-up, the patient remained symptom free, the periapical region was completely healed, inhibition of the root resorption process achieved, and formation of the new periodontal ligament as well as tooth widening development observed, meeting functional expectations after 48 months. The regenerative endodontic procedures are an available option to treat IRR in severely immature teeth. The available literature on the regenerative endodontic procedures applied to IRR treatment is limited, and more research is needed in this field.